Prevalence and Molecular Characteristics of Carbapenem Resistant Acinetobacter baumannii Isolates from A Regional Tertiary Care Hospital: Life Science-Microbiology - E, Fiji; B, Anandharaj; G Varghese, Jijo (International Journal of Life Science and Pharma Research, 2022)
Acinetobacter spp., is an emerging opportunistic nosocomial Gram negative bacterial pathogen with increasing prevalence in particular the species Acinetobacter baumannii. It infects the most vulnerable immunocompromised hospitalized patients who are critically ill. Significant levels of morbidity and mortality have been reported with outbreaks and the carbapenem hydrolyzing beta lactamases that includes MBLs and oxacillinases are recognized as important contributors of carbapenem resistance in Acinetobacter spp., Enzymatic degradation of drugs, target modifications, multidrug efflux pumps and permeability defects are some of the important resistance mechanisms present in A. baumannii. Accumulation of various resistance mechanisms made treatment of A. baumannii infection very difficult. The major objective of the study was to identify the pattern of antibiotic resistance and its regional prevalence. Hence this study was aimed and conducted to isolate, identify and distinguish the antibiogram of A. baumannii from clinical specimens and to study a molecular level identification of resistance mechanisms of the isolates from a tertiary care hospital. Various clinical specimens like blood, urine, abscess, vaginal swab were analyzed and evaluated for the presence of Acinetobacter. Four members of Acinetobacter species; A junii, A lowffii, A ursingii and A baumannii, were isolated from clinical specimens. A. baumannii was the predominant species and 15% of the A. baumannii isolates were confirmed to be resistant to carbapenems. A molecular typing was done to identify the genes conferring antibiotic resistance and five major genes were identified in the isolates. The predominant genes present in the isolates wereOXA-58, OXA-23 and GIM. Presence of IMP & VIM were also identified. , ,